2022
DOI: 10.3389/fenvs.2022.1001064
|View full text |Cite
|
Sign up to set email alerts
|

Spatio–temporal evolution and factors of climate comfort for urban human settlements in the Guangdong–Hong Kong–Macau Greater Bay Area

Abstract: This study used both temperature-humidity and wind efficiency indices at three time-scale resolutions (year, season, and month) for the first time, to analyze the spatio–temporal evolution of urban climate comfort in the Guangdong–Hong Kong–Macau Greater Bay Area (GBA). The main factors affecting human-settlement climate comfort were elucidated and the annual changes in both indices used in the study area exhibited fluctuating growth from 2005 to 2020. Moreover, the annual growth of the temperature-humidity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…However, in some countries worldwide, including those in the Global South, global warming issues might cause population decline. Particularly, researchers show that there are correlations between the urban population, the built environment, and land surface temperatures [ 39 42 ], and that land surface temperatures are influenced more by the built than natural environment [ 43 ]. Another study shows that the relationship between these factors and urban temperature is nonlinear [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some countries worldwide, including those in the Global South, global warming issues might cause population decline. Particularly, researchers show that there are correlations between the urban population, the built environment, and land surface temperatures [ 39 42 ], and that land surface temperatures are influenced more by the built than natural environment [ 43 ]. Another study shows that the relationship between these factors and urban temperature is nonlinear [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…there are correlations between the urban population, the built environment, and land surface temperatures [39][40][41][42], and that land surface temperatures are influenced more by the built than natural environment [43]. Another study shows that the relationship between these factors and urban temperature is nonlinear [44].…”
Section: Plos Onementioning
confidence: 99%
“…The impact of digital economy on modern society is profound and extensive. The development of digital economy can not only improve air quality, ease heat island and carbon emissions, enhance climate comfort [1][2][3][4], but also bring revolutionary changes to existing business models [5]. With the acceleration of the integration of information technology and real economy, the application of information technology and the Internet constitutes an important factor affecting the efficiency of contemporary economic growth [6].…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of urban ventilation to the thermal environment and the urban energy demand have been taken seriously [ 12 ]. The spatiotemporal relationship between the climate comfort of the urban human settlement environment and population density in China has also received much attention [ 13 , 14 ]. These studies revealed that climate change is of great significance to human society.…”
Section: Introductionmentioning
confidence: 99%